2008
DOI: 10.1890/07-1292.1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Bee Diversity in Different European Habitats and Biogeographical Regions

Abstract: Bee pollinators are currently recorded with many different sampling methods. However, the relative performances of these methods have not been systematically evaluated and compared. In response to the strong need to record ongoing shifts in pollinator diversity and abundance, global and regional pollinator initiatives must adopt standardized sampling protocols when developing large‐scale and long‐term monitoring schemes. We systematically evaluated the performance of six sampling methods (observation plots, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
642
7
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 653 publications
(670 citation statements)
references
References 69 publications
16
642
7
5
Order By: Relevance
“…Research by Menalled, Marino, Gage, & Landis (1999) found that complex landscape had higher diversity of parasitoids Braconidae than in simple landscape. In this study, abundance of flowervisiting insects did not differ between complex and simple landscape, a similar result to Westphal et al (2008) who found landscape complexity, characterized by the proportion of semi-natural habitat, did not affect the abundance of bees. Instead, abundance of bees was more affected by the occurrence of flowering plants in the landscape.…”
Section: Effect Of Landscape Complexity On Species Richness Abundancsupporting
confidence: 89%
See 1 more Smart Citation
“…Research by Menalled, Marino, Gage, & Landis (1999) found that complex landscape had higher diversity of parasitoids Braconidae than in simple landscape. In this study, abundance of flowervisiting insects did not differ between complex and simple landscape, a similar result to Westphal et al (2008) who found landscape complexity, characterized by the proportion of semi-natural habitat, did not affect the abundance of bees. Instead, abundance of bees was more affected by the occurrence of flowering plants in the landscape.…”
Section: Effect Of Landscape Complexity On Species Richness Abundancsupporting
confidence: 89%
“…The weather condition were predominantly clear sky, no rain, low wind and dry vegetation (Westphal et al, 2008). In each cucumber field, four transects were selected for insect sampling (Fig.…”
Section: Sampling Of Flower-visiting Insectsmentioning
confidence: 99%
“…Each transect was visited three times for 135 min per transect from July to August. Therefore, for this species, the sampling effort was different for each flowering plant species (Westphal et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Each study site was sampled using a variable transect walk method (Westphal et al, 2008). For this method, the surveyors walked slowly among any potentially attractive resource patches and collected bees during a 120 min observational period.…”
Section: Flowering Plant Composition and Abundancementioning
confidence: 99%